1985
DOI: 10.1111/j.1468-2958.1985.tb00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Conversational Complexity

Abstract: A successful conversation requires participants to have knowledge of both the topic under discussion and the nature of conversation. This study asks whether people who are more sophisticated in their representation of conversation behave differently than their less sophisticated counterparts. This issue was probed by devising two operationalizations of what we call Conversational complexity. The two measures assessed peoples' constructs about conversation (operationalized by a measure of construct differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Thus, implementing two or more interventions not only reduces anxiety over single interventions but also reduces high CCA's anxiety to a level also experienced by select low CCA groups. Findings for ambiguity reduction are opposite Booth-Butterfield's (1986) and others (Daly, Bell, Glenn, & Lawrence, 1985;Stafford & Daly, 1984) who report that high CA's perform better under highly structured conditions. It could be argued that student-generated questions assist CCA's in structuring discussion, thus reducing their ambiguity reduction, or that responding to the instructor's questions may signal evaluation potential if students perceive the instructor attempting to structure discussion, which they may infer simply from having a list of questions to prepare.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, implementing two or more interventions not only reduces anxiety over single interventions but also reduces high CCA's anxiety to a level also experienced by select low CCA groups. Findings for ambiguity reduction are opposite Booth-Butterfield's (1986) and others (Daly, Bell, Glenn, & Lawrence, 1985;Stafford & Daly, 1984) who report that high CA's perform better under highly structured conditions. It could be argued that student-generated questions assist CCA's in structuring discussion, thus reducing their ambiguity reduction, or that responding to the instructor's questions may signal evaluation potential if students perceive the instructor attempting to structure discussion, which they may infer simply from having a list of questions to prepare.…”
Section: Discussioncontrasting
confidence: 54%
“…Daly, Bell, Glenn, and Lawrence (1985) suggested that subjects are only likely to remember about 10% of a conversation accurately. If those being briefed become bored and do not pay attention to the briefer, then any impact on behaviour is likely to be significantly reduced.…”
Section: Research On Effective Superior6subordinatementioning
confidence: 98%
“…Researchers have speculated that sensitivity to conversations is associated with having a wide variety of communication experiences. Communication experiences should broaden one's categories for interaction behavior and enhance awareness of communication [31]. One way that sensitivity might be enhanced is by individuals having pro and retroactive, linked lIs in order to interpret what previously occurred in an encounter while preparing or envisioning a future encounter.…”
Section: Imagined Interaction Conversational Sensitivity Communicatmentioning
confidence: 97%